Age-dependent effects of a high-fat diet combined with dietary advanced glycation end products on cognitive function and protection with voluntary exercise. Issue 8 (28th March 2022) - Luo, Lan; Li, Rui; Wang, Guiping; Chen, Jingsi; Chen, Liangkai; Qin, Li-Qiang; Yu, Zengli; Wan, Zhongxiao
Abstract : Compared to HFD, HFD combined with an AGEs diet induced worse memory abilities only in middle-aged mice. Voluntary exercise effectively reversed the impaired cognitive performance from both age of mice, but differential mechanisms were observed. Abstract : To determine whether a high fat diet (HFD) combined with an advanced glycation end products (AGEs) diet will induce worse cognitive impairment than a HFD alone and to investigate whether voluntary exercise is capable of improving cognitive function after the combined diet, young and middle-aged male C57BL/6J mice were randomly assigned to four groups, i.e., control, HFD, combined diet, and combined diet treated with voluntary exercise. Compared to HFD, combined diet induced worse memory abilities only in middle-aged mice, as exhibited by the reduced number of crossings and reduced distance in the target zone during a probe trial. Exercise reversed combined-diet-induced cognitive impairment for both ages of mice. For young mice, the neuro-protective effects of exercise were mainly associated with inhibition of NLRP3, Dnmt3a, Dnmt3b, and H3K9me2 and elevation of OST48; it also elevated Bacilli and reduced Epsilonproteobacteria, Campylobacterales, and Helicobacter . For middle-aged mice, exercise elevated Tet2, inhibited NF-κB and NLRP3, and rebalanced circadian clock proteins and the RAGE-OST48 axis; also, exercise elevated Coriobacteriia / Coriobacteriaceae, Erysipelotrichaceae, and Allobaculum and restored intestinal permeability.